Integration of Soft Systems Methodology and System Dynamics Modelling for Supply and Demand Analysis of the Rising Cost in Higher Education - Nurul Nazihah Hawari (International Journal of Supply Chain Management, 2018)
Consumer price index in Malaysia is showing the rising expenses on education. The rising cost in higher education provision is among factors that contribute to the rising expenses on education. This paper develops a model of supply and demand in higher education using the integration of soft systems methodology and system dynamics to analyse this issue. The findings from this research helps in gaining insight to understand the dynamic behaviour of supply and demand in higher education provision and the implication of the rising cost towards higher education supply and demand.